Investigation of surface interactions of pyrazinamide and pyrazinoic acid with synthetic and natural lipid membrane model systems - Gasparovic, Nathaniel, author; Crans, Debbie C., advisor; Henry, Chuck, committee member; Ryan, Elizabeth, committee member (Colorado State University. Libraries, 2022)
Pyrazinamide (PZA) is a pro-drug used in the treatment of tuberculosis. Upon administration of the drug, it is converted to its active form of pyrazinoic acid (POA) by the tuberculosis bacterium; this is believed to be the biologically active form of the drug which exerts anti-tubercular activity. However, it is generally accepted that both compounds interact with and transverse the membrane, with POA potentially functioning as a protonophore and lowering the intracellular mycobacterial pH. To investigate the interactions of PZA and POA in model membranes, we employed Langmuir monolayers to investigate the potential membrane-disrupting effects of PZA and POA on a model membrane. At physiological pH, neither PZA nor POA disrupted the membrane, although a difference in compressibility was observed. At acidic pH, POA became more disruptive but only at high, non-physiological concentrations. 1H NMR spectroscopy of a microemulsion system was used to investigate the location of PZA and POA in the interface in different protonation states. The neutral POA species was found to preferentially reside in the interface while the charged species remained in the interfacial water. Finally, the effects of PZA and charged POA on the bilayer in liposomes were investigated. A leakage assay on fluorophore-filled liposomes showed that PZA and POA do not induce leakage in the membrane at physiological conditions.
Zip file contains SI for PZA/POA.